UNDERSTANDING THE ROLE OF PAIR PROGRAMMING IN AGILE TEAM DYNAMICS - Sameena Tabbsum; Syed Zaffar Iqbal; Palwasha Khalid (Spectrum of Engineering Sciences, 2025)
Background and Purpose: Pair programming, a core practice in agile software development, has gained attention for its potential to enhance team collaboration and code quality. However, there is limited qualitative understanding of how pair programming influences team dynamics, communication, and interpersonal relationships within agile environments. This study aims to explore the role of pair programming in shaping agile team dynamics from the perspective of software developers. Methods: A qualitative research approach was employed, using semi-structured interviews with twelve software developers working in agile teams across multiple software firms. Thematic analysis was applied to interpret the data, allowing for in-depth exploration of participants’ lived experiences and perceptions related to pair programming practices. Key Findings: The findings revealed that pair programming contributes positively to team cohesion, knowledge sharing, and problem-solving efficiency. It fosters mutual learning, improves real-time feedback loops, and builds stronger interpersonal connections. However, challenges such as personality clashes, fatigue, and varying skill levels can impact its effectiveness. The study highlights the importance of adaptability and team culture in maximizing the benefits of pair programming. Conclusion: Pair programming plays a significant role in enhancing agile team dynamics by strengthening collaboration and learning processes. For optimal impact, organizations should consider team composition, pairing strategies, and periodic rotation to balance productivity and team satisfaction.